2021
DOI: 10.3390/met11101553
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High-Pressure Torsion on the Microstructure and Microhardness of Additively Manufactured 316L Stainless Steel

Abstract: High-pressure torsion (HPT) is known as an effective severe plastic deformation (SPD) technique to produce bulk ultrafine-grained (UFG) metals and alloys by the application of combined compressive force and torsional shear strains on thin disk samples. In this study, the microstructures and microhardness evolution of an additively manufactured (AM) 316L stainless steel (316L SS) processed through 5 HPT revolutions are evaluated at the central disk area, where the effective shear strains are relatively low comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Austenitic stainless steels have austenite (FCC) phase at room temperature, are low stacking fault energy (SFE) materials, and their plastic deformation at low temperatures occurs through several mechanisms simultaneously. These steels have been extensively studied using SPD (51,52,53,54,55,56) , and it has been shown that various deformation mechanisms are present, depending on the SFE of the material and the processing conditions such as deformation temperature. The initial phase (γ-austenite) gradually transforms to ɛ-and α'-martensite due to deformation.…”
Section: Stainless Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…Austenitic stainless steels have austenite (FCC) phase at room temperature, are low stacking fault energy (SFE) materials, and their plastic deformation at low temperatures occurs through several mechanisms simultaneously. These steels have been extensively studied using SPD (51,52,53,54,55,56) , and it has been shown that various deformation mechanisms are present, depending on the SFE of the material and the processing conditions such as deformation temperature. The initial phase (γ-austenite) gradually transforms to ɛ-and α'-martensite due to deformation.…”
Section: Stainless Steelmentioning
confidence: 99%
“…The formation and adhesion of passive films on 316L SS processed using HPT have also been reported. The larger amount of grain boundaries, dislocation density, and higher residual stresses provide nucleation sites for the passive oxide layers to become more stable (52) . Yusuf et.…”
Section: Stainless Steelmentioning
confidence: 99%
“…Up to now, several studies have been investigated on enhancing the hardness/strength of L-PBF AM metallic materials by SPD processes, specifically that of 316L SS [11,12], AlSi10Mg [13,14], and IN 718 [15]. However, there is a lack of study on the effects of SPD, particularly HPT on the combined microstructure, hardness, and corrosion performance, especially on AM-fabricated IN 718.…”
Section: Introductionmentioning
confidence: 99%